The higher education magers handbook: effective leadership and management in universities and colleges - McCaffery, Peter
The Higher Education Manager?s Handbook 2/e has been substantially updated and reflects important changes that have occurred since its first publication in 2004. It offers excellent counsel and guidance on all aspects of the manager?s role and provides the navigational tools to successfully operate within Higher Education organizations. Within this new edition, Peter McCaffery continues to draw on a wealth of US and UK case study materials drawn from innovative practice. This best selling guide builds upon its original strengths and remains an engaging, accessible and highly enjoyable read. Written in the unique perspective of the HE manager, it offers practical advice that can be implemented immediately by managers and university leaders at all levels. It addresses the internal ramifications of cynicism and demoralisation that are rife within many academic communities and is based on four pre-requisites essential for becoming an effective HE leader.